Robust Control of Three-Phase VSI with LCL Filter for Distributed Generation Power Quality Improvement - Peña, José Carlos Ugaz [UNESP]; Sampaio, Leonardo Poltronieri; de Brito, Moacyr Aureliano Gomes; Canesin, Carlos Alberto [UNESP] (Springer Nature, 2020)
This paper proposes a methodology to control a three-phase voltage source inverter with LCL filter for distributed generation (DG) in microgrid scenario. Thus, the presented control strategy allows the DG system to operate in both grid-connected and islanded modes with a smooth transition between them. Therefore, the DG control system strategy is performed by splitting the control input into two control-stages; the first one is in charge of reproducing sinusoidal voltages at the filter capacitors; meanwhile, the second is dedicated to modulate these voltages in order to achieve proper amplitude and phase for correct output current injection. By means of discrete-time state-space representation of the system, state-feedback controllers are obtained employing linear matrix inequalities considering uncertainties on grid inductances and optimization of the H2 norm for each operation mode. Finally, the feasibility of the proposed DG system is demonstrated and validated through computational simulations, as well as experimental evaluations.
Keywords: Grid-connected inverter; LCL filter; Linear matrix inequalities (LMIs); Microgrid inverter; Robust control